The transferability of the minimal invasive surgeon's skills to open surgery - Ordell Sundelin, Maria; Paltved, Charlotte; Kingo, Pernille Skjold; Blichert-Refsgaard, Linea; Lindgren, Maria S.; Kjölhede, Henrik; Jensen, Jørgen Bjerggaard (Scandinavian journal of urology, 2022)
Robot-assisted laparoscopic surgery has gained popularity, which has contributed to a decrease in the number of open procedures. Hence a growing concern regarding the ability of laparoscopically trained surgeons to perform open surgery (e.g. due to bleeding complications) has been raised. The aim of the study was to investigate the ability of conversion to open surgery following exclusively robotic or laparoscopic training. Thirty-six medical students were randomized into three groups: Open surgery, laparoscopy, and robot-assisted laparoscopy. All underwent intensive simulation training in the allocated surgical modality. Subsequently, all study subjects performed an open bowel anastomosis in a pig model where anastomoses were tested for resistance to pressure and leak as a surrogate marker of surgical quality. The primary endpoint was the surgical quality of an open surgery model assessed as, leak pressure, which was 80.01 ± 36.16 mmHg in the laparoscopic training group, 106.57 ± 23.03 mmHg in the robotic training group, and 133.65 ± 18.32 mmHg in the open surgery training group (mean, SD). We found that there were no significant differences between the open surgery training group and the robotic training group whereas a significant difference was found when comparing laparoscopic and open surgery training groups in favor of open procedure training (p < 0.001). In a surrogate open surgery model based on bowel anastomosis, we found that skills acquired through practice on robotic simulation platforms were not significantly worse when compared to skills acquired through training in open surgery, whereas skills acquired from laparoscopic training were significantly poorer when compared to open surgery practice.